Campesino a Campesino (peasant to peasant) processes versus conventional extension: a comparative model to examine agroecological scaling - Bernal, David; Giraldo, Omar Felipe; Rosset, Peter M. [UNESP]; Lopez-Corona, Oliver; Perez-Cassarino, Julian (Taylor & Francis, 2023)
An important question in agroecology is that of social process methodology to achieve scaling. Despite the great achievements of the Campesino a Campesino (CaC) (peasant to peasant) methodology to multiply agroecological practices among the peasantry, many experiences continue to use the technical assistance conventional extension model, which consists of hiring technicians for a public sector institution, an international organization or a Non-Governmental Organization (NGO) to “transfer” agroecological practices to their clients or beneficiaries. CaC, instead, is designed to establish a network of farmers who share their own practices with each other, and the role of the technician changes to that of facilitator in the design and execution of the overall process. In this article we present a model in which we simulated the experience of the National Association of Small Farmers (ANAP) in Cuba and compared it with conventional extension, systematically exploring which properties make CaC a more effective, less costly and more dynamic methodology for territorializing or scaling agroecology.
Keywords: agricultural extension; Campesino a Campesino (peasant to peasant); diffusion of agroecology